Towards Nostalgic Reading of Children's Literature in Academic Teaching - Monika Kupiec (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: The need to recognize the student's way of reading children's reading is related to planning the development in the course of academic education of important methodological skills of the future teacher of early education (selection of literary texts, organization of work with the text). Every early childhood teacher is a nostalgic go-between for children's literature. Research Aim: The aim of my own research is to identify students' opinions about selected texts of children's literature. Particular attention was paid to identifying revealed reading strategies. Method: The method of personal documents was used. The impulse that triggered students' reflection on their own opinion about a children's book was writing a review of a selected reading. Results: 41 student statements were collected. Among the reviewed items, the vast majority (in 31 reviews) were literature considered classic, which has been included in the recommendations of the core curriculum for years. The analysis shows that 14 people read the reviewed books in childhood and declared that they read them again in their adult life. The analysis of students' choices reveals a lack of knowledge of children's books published after 2006, i.e. during their early education. The most frequently activated strategy of receiving children's literature - regardless of the baggage of experience related to reading a given book in childhood - is infantilizing reading. Conclusion: Without identifying the strategy of reading children's literature, future teachers will not be able to participate competently in the child's literary communication, even with personal "reading". Intensifying the critical reading of children's literature in academic classes for future teachers of early childhood education seems to be a good way to collect reading experiences and prepare for the role of a mediator of reading. Critical reading activities can be intensified in the activities of circles, laboratories and children's book discussion clubs for future teachers of early childhood education.